Produktivitas Kambing Peranakan Etawah yang Diberi Ransum Berbasis Jerami Padi Fermentasi - C I Novita; A Sudono; I K Sutama; T Toharmat (Faculty of Animal Science, Bogor Agricultural University, 2006)
Rice straw as one of agriculture by product has low nutritive value. Fermentation of rice straw increased its nutrient digestibility and palatability. Present experiments aimed to study the effect of feeding rations composed of concentrate and ground fermented rice straw supplemented with urea and probiotic. The first trial was conducted to study the apparent digestibility of experimental diets in 18 Etawah-grade bucks with 1-1.5 year age and initial body weight of 30.18 ± 8.38 kg. The second trial was conducted to study the effect of feeding experimental rations on reproduction, milk yield and its quality in 24 Etawah-grade does with 1 to 3 years age and initial weight of 35.75 ± 5.72 kg. The rations were as follows; KJP = concentrate + chopped fermented rice straw; KJG = concentrate + ground fermented rice straw; KRG = concentrate + elephant grass. A completely randomized design was applied in both nutrient digestibility and performance trials. In both trials, the rations were offered twice daily. Does and kids were weighted once in two week. Does were milked manually once a week for 3 months post partum. Milk was sampled for determination of its specific gravity, protein, fat and solid content. Gestation length, litter size, birth weigth and weaned weight were recorded. Dry matter (DM) and crude protein (CP) intake, and apparent digestibility of DM did not differ significantly among treatments. However, apparent digestibility of CP in goat offered KJG was lower (P < 0.05) than those of KRG and KJP. DM and CP intake of does was higher (P < 0.05) for the KRG treatment but those were not differ between KJP and KJG treatments. Gestation length, litter size, the body weight of does during pregnancy and lactation, the body weight of kids from birth to weaning, milk yield and quality of milk were not different ammong tretaments. These results suggested that fermented rice straw can be used to substitute the elephant grass. Key words: Goat, straw, fermentation, digestibility, milk, kids